Penetration Testing and Vulnerability Analysis of SINTA Platform to Strengthen Privacy and Data Protection - Supangat Supangat; Anis Rahmawati Amna; Mochamad Yovi Fatchur Rochman (Journal of Information Technology and Cyber Security, 2025)
The increasing reliance on digital platforms for academic and governmental purposes necessitates robust cybersecurity measures. Consequently, identifying vulnerability is critical to ensuring data security and providing actionable recommendations for cybersecurity officers. Platforms like Sinta (Science and Technology Index), which focus on collecting peer-reviewed papers and maintaining researcher’s research records, represents significant governmental contributions in academia. Cybersecurity awareness is demonstrated through events organized to evaluate the vulnerability of the platform, enabling researchers to access its security and report potential issues. This study addresses these concerns by conducting system penetration testing using the OWASP and Burp Suite Framework, focusing on identifying five critical vulnerabilities. The evaluation examines issues, such as sensitive data exposure in API responses, error log disclosures, email enumeration, and improper access to system files. The results reveal that the platform suffers from multiple levels of security vulnerabilities, prompting recommendations for authorities to take actions to mitigate potential risks effectively.